ANALISIS TINGKAT BAHAYA EROSI DI DAERAH ALIRAN SUNGAI KAMPAR BAGIAN HULU - Mitri Irianti; Besri Nasrul; Idwar Idwar (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2018)
The upstream of Kamparwatershed represent the part of Siak Watershed in the Province ofRiau which has been degradated.This research aims to determine the location, wide, anddegree of the land criticality according to the erosion hazard level in the upstream ofKampar watershed. So the research can determine the way, type, and priorities ofwatershed management. This research used survey method and laboratory analysis of soilsamples. The survey was done by observing the land use and conservation applied to theland unit. The data collected were rainfall, soil characteristics, slopes, crop management,and land conservation techniques. The obtained data were analyzed using the USLEformulation to define the erosion hazard level of the upstream Kampar watershed. Theresults found that the erosion of the upstream Kampar watershedis in the high category.The best practices to reduce the level of erosion hazard in the upstream Kampar watershedare improving the crop management and land conservation techniques in an integratedmanner on each land unit.